Medico-social aspects of hepatocellular carcinoma - Niyaz Malayev; Samat Saparbayev; Saule Kubekova; Nurgul Kereyeva (National Scientific Medical Center, 2023)
Oncological diseases are one of the leading health problems both in the world and in Kazakhstan, second only to cardiovascular diseases. Hepatocellular carcinoma occupies the 8th place in the structure of oncopathologies, has an unfavorable prognosis and an unfavorable course. According to the WHO, more than 1.3 million people die each year from hepatocellular carcinoma (HCC). The incidence rate of HCC in Kazakhstan is up to 5.5 cases per 100 thousand of the population, and the mortality rate remains high (about 1000 people annually). In 2017, 82.3% of HCC patients died before the end of the year. Five-year survival in HCC does not exceed 18%, and postoperative recurrence is about 50%.